Health Status of Seagrass Meadows Around the Special Economic Zone (SEZ), West Likupang, North Sulawesi - Satriani; Zulhamsyah Imran; Fery Kurniawan; Perdinan; Akbar Ario Digdo (Jurnal Penelitian Pendidikan IPA, 2024)
Seagrass ecosystems offer valuable ecosystem services but are highly vulnerable to physical damage caused by human activities and rapid environmental change. Currently, there is very limited information available on monitoring and reporting the health of seagrass beds in Indonesian waters. This study aims to assess the species composition, density, diversity index, percentage of seagrass cover, health condition, and identification of threats to seagrass ecosystems around the West Likupang Special Economic Zone (SEZ), North Sulawesi. The method used was a seagrass watch with line transects and quadrant-shaped frames measuring 50x50 cm2. Transect lines were established through the seagrass ecosystem area at 50 m. There were three line transects at each station 25 m apart. Quadrant frame measuring 50x50 cm2. West Likupang has eight seagrass species including C. rotundata, E. acoroides, H. pinifolia, H. uninervis, H. ovalis, O. serrulata, S. isoetifolium, dan T. hemprichii. The health status of the seagrass is currently healthy, with a dense percentage of coverage. The identification of potential risks from anthropogenic activities such as the household disposal of waste at sea, gleaning, the use of boat anchors and propellers, and the construction of infrastructure in coastal areas, such as hotels and harbonurs, pose significant threats.